Phytolith Assemblages Along a Gradient of Ancient Human Disturbance in Western Amazonia - McMichael, Crystal H.; Piperno, Dolores R.; Neves, Eduardo G.; Bush, Mark B.; Almeida, Fernando O.; Mongeló, Guilherme; Eyjolfsdottir, Margret B. (Frontiers in Ecology and Evolution, 2015)
The ecological status of prehistoric Amazonian forests remains widely debated. The concept of ancient Amazonia as a pristine wilderness is largely discredited, but the alternative hypothesis of extensive anthropogenic landscape remains untested in many regions. We assessed the degree of ancient human impacts across western Amazonia based on archaeological and paleoecological data using methodologies that would allow inter-regional comparisons. We also aimed to establish baselines for estimating the legacies of ancient disturbances on modern vegetation. We analyzed charcoal and phytolith assemblages from soil samples from an archaeological site, sites in close proximity to archaeological sites, sites from riverine and interfluvial forests, and a biological research station believed to contain some of the least disturbed forests within Amazonia. We then quantitatively compared phytolith assemblages within and between the surveyed regions. Palm enrichment was evident at the archaeological site, and the biological station survey contained little to no evidence of ancient human activity. The other sites exhibited a gradient of ancient disturbance across the landscape. The phytolith assemblages showed statistically significant between-region variations that indicated our metrics were sufficiently sensitive to detecting ancient disturbance. Our data highlight the spatial heterogeneity of ancient human disturbances in Amazonian forests. The quantification of these disturbances provides empirical data and a more concrete link between the composition of the modern forest and ancient disturbance regimes. Accounting for ancient disturbances will allow a deeper understanding of the landscape heterogeneity observed in the modern forests.